Removal of coke precursors with hydrogen: Studies with alternating pulses of propane and hydrogen - Tauster, Samuel J; Koros, Robert M (Journal of catalysis, 1972)
The time scale of coke formation on the surface of a supported chromia catalyst, during the dehydrogenation of propane at 1200 °F, has been studied. The reactor feed consisted of alternating pulses of propane and hydrogen. For switching frequencies as high as 1 sec −1, the catalyst bed did not destroy the pulsed nature of the feed. A model of residue formation is discussed which involves growth of unsaturated oligomers, which upon reaching a critical size can no longer be regenerated with hydrogen. The time required for the development of such a species is found to be of the order of 1 sec.